Galilee eaudiobook A novel of the fantastic. - Barker, Clive (Recorded Books Inc., 1999)
A successful film maker, painter, playwright, and best-selling author, Clive Barker commands an astonishing range of creative talent. Drawing upon the literary genius that produced Sacrament, he returns to the realm of the supernatural with this intriguing saga of two families, one human and the other divine. One of America's wealthiest and most influential families since the Civil War, the Gearys harbor terrible secrets. The Barbarossa family's roots are far more ancient and ethereal, but they are bound to the Gearys by a shared history of murder, insanity, and adultery. When Rachel Geary and Galilee, the seductive prince of the Barbarossa clan, fall in love, they unleash powerful enmities that could destroy both dynasties. Shorter and more conventional than some of Barker's other work, this novel is especially rich with complex, passionate, three-dimensional characters, lush settings, and elegant language. Paul Hecht's powerful narration gives added depth to this dark, sumptuous novel.